Psicomotricidad gruesa y su impacto en el desarrollo integral de los niños de educación inicial en la Unidad Educativa Francisco Huerta Rendón - Quisintuña Sandoval, Gilda Jamilex (2023)
Psychomotricity is one of the processes of great importance for the integral development of children, understanding integrality as the set of curiosity, intellect, spontaneity, creation of emotions, art, philosophy, beliefs, which through movements (psychomotricity) such as running, walking, turning, grasping or using the hands, extremities, facilitates the involvement of the child in the world that surrounds him, therefore gross psychomotor skills and its impact on the comprehensive development of education children are raised as a research topic. in the Francisco Huerta Rendón Educational Unit, whose objective is to determine the impact of gross psychomotricity in the integral development of children in initial education, in order to carry out the research it was necessary to use the quantitative approach to obtain the results in which could determine the existence of several problems that can be observed in the discussion of the results to In addition to concluding with the fulfillment of the objective and the elaboration of the recommendations according to the situation.